Effect of chronic alcohol consumption on the morphology of the oral mucosa - Maier, Heinz; Weidauer, Hagen; Zöller, Joachim E.; Seitz, Helmut K.; Flentje, Michael; Mall, G.; Born, Ivan Antonio (Alcoholism, 1994)
Chronic alcohol consumption is a major risk factor for oral and pharyngeal cancer. Besides other mechanisms a toxic effect of ethanol and/or its metabolite acetaldehyde on the oral mucosa and resulting increased cell regeneration seem to play an important role in tumor promotion. In the present study the effect of chronic ethanol consumption on the morphology of the oral mucosa of 40 male wistar rats that had been fed nutritionally adequate liquid diets containing 36% of total calories either as ethanol or isocaloric carbohydrates for 6 months was investigated. Morphometric analysis showed that in the ethanol rats the size of the basal cell nuclei of the oral mucosa from the floor of the mouth, the edge of the tongue and the base of the tongue were significantly enlarged (p < 0.001). The size of the basal cell layer in these rats was increased, and the stratification of the cells was altered. The percentage of cells in the S-phase of the cell cycle was significantly higher in the ethanol-fed rats (p < 0.01). Mean epithelial thickness of the mucosa from the floor of the mouth was significantly reduced in the ethanol rats (p < 0.01). In conclusion, the reported findings indicate, that chronic ethanol consumption causes oral mucosal atrophy associated with hyper-regeneration, which may result in an enhanced susceptibility of the mucosal epithelium toward chemical carcinogens.